(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2018)
A total of 1.899 samples of hake (Merluccius gayi) were collected during 2014 by the artisanal fishery using the bottom spinel as a fishing gear in Anconcito, in the province of Santa Elena. The samples were classified as 630 males (33.25%) and 1.269 females (66.75%), the results indicate that the presence of females was higher than that of males, that was evidenced by the sexual proportion of 1: 2.01. Prionotus stephanophrys was the species with the highest percentage (79.7%) in the catch composition of associated fauna. Regarding to sexual maturity, samples of Merluccius gayi showed the highest dominance at stages III and V. The average length of maturity of the population of females of Merluccius gayi was determined at 31 cm of Lt. The resulting data suggests that a biological fishing follow-up must be carried out to establish an adequate management of this resource.